Photonic crystal fiber (PhCF) for petrochemical sensing - Hossain, Md. Bellal; Kříž, Jan; Dhasarathan, Vigneswaran; Rahaman, Md. Ekhlasur (Frontiers in Physics, 2023)
A square-core photonic crystal fiber (PhCF) has been presented for liquid (petrochemical) sensing application. The sensor performance has been studied numerically in the frequency range from 1.2 to 3.8T Hz. The core hole is filled with pure petrol, kerosene and diesel. Strut size is varied to explore the sensor’s performance and the analysis is performed in terahertz (THz) frequencies. The PhCF sensor shows a relative sensitivity of around 97.0% and a confinement loss in the order of 10−14 at 3.7T Hz. This PhCF sensor can be fabricated using extrusion and 3D-printing technologies.